Entrainment of particle from a cavity - Boon, Chia Hui. (2011)
The construction of armor layers on an erodible loose bed is a common method to prevent scour in a river for the protection of hydraulics structures. However, the stability of these armor layers is susceptible to winnowing in which material from between or underneath armored beds will be sucked out, resulting in an irregular lowering of the bed’s elevation.To prevent failure due to winnowing effects, a substantial amount of researches have been conducted to investigate the mechanism of winnowing failure with an armored bed. A previous study conducted by Chen (2010) showed that the entrainment of a single particle in a rectangular cavity follows the probability distribution model instead of a deterministic one.